Intestinal intussusceptions in children population - Kopystecka, Agnieszka; Kopeć, Izabela; Mitek-Palusińska, Joanna; Woźniak, Magdalena Maria (Journal of Education, Health and Sport, 2022)
Intussusception is an invagination of a proximal segment of the bowel into an immediately adjacent, distal portion of the bowel. Ileocolic intussusception is one of the most common causes of bowel obstruction in children. The peak incidence occurs in infants between five and seven months of age. The etiology of intussusception in children is typically idiopathic, approximately 5-10% of patients have a pathological lead point. Postoperative intussusception is one of the rare causes of intussusception. Children with ileocolic intussusception often present abdominal pain, palpable mass, rectal bleeding, fussiness, and emesis. The most effective imaging method for the diagnosis of intussusception is ultrasound. The treatment of ileocolic and ileoileal intussusceptions is different, the first type requires invasive treatment.